Status Gizi Serta Hubungannya Dengan Kejadian Diare Pada Anak: Nutritional Status And Its Relationship With The Incidence Of Diarrhea In Children - Faticha Zakiya; Irfana Tri Wijayanti; Yuli Irnawati (YCMM, 2022)
Diarrhea is a major cause of morbidity and mortality in children in developing countries. The main cause of death due to dehydration as a result of loss of fluids and electrolytes through the feces. Other important causes of death are dysentery, malnutrition and serious infections such as pneumonia. Based on the results of the preliminary study that has been carried out there are 20 mothers who have toddlers who visit the Work Area of ​​the Dukuhseti Health Center, Pati Regency, namely there are 8 respondents who have mothers who suffer from diarrhea due to food factors and the behavior of the children themselves with a weight of 2.1-13.6 kg (aged 1-5 years) and it was found that 12 respondents who had children under five stated that their children had not paid attention to their nutritional status or had poor nutrition with a weight of 1.7-11.7 kg (aged 1-5 years). The purpose of this study was to determine nutritional status with the incidence of diarrhea in children under five. This type of research uses correlation analysis with a cross sectional approach. The population in this study were all children under five who visited during January-March 2020 as many as 673 toddlers. The samples taken were 67 toddlers. The sampling technique used is Random Sampling (randomly). Result of research : Respondents whose nutritional status is less affected by diarrhea are 26 toddlers (38.8%) and 10 toddlers (14.9%). Meanwhile, 2 (3.0%) respondents with poor nutritional status had diarrhea and 0 (0.0%). The results of the chi square test obtained count 17.030 > table 5.9915 and p value 0.001 <0.05. It can be concluded that Ho is rejected and Ha is accepted which means that there is a significant relationship between nutritional status and the incidence of diarrhea in children under five.